Respuesta :
Step-by-step explanation:
Consider the provided function.
[tex]f(x)=4(\frac{1}{3})^{2x}[/tex]
Apply exponent rule: [tex]\left(\frac{a}{b}\right)^c=\frac{a^c}{b^c}[/tex]
[tex]f(x)=4(\frac{1^2}{3^2})^x[/tex]
[tex]f(x)=4(\frac{1}{9})^x[/tex]
Hence, the required function is [tex]f(x)=4(\frac{1}{9})^x[/tex]
OR
If the function is [tex]f(x)=4(\frac{1}{3})^2x[/tex]
Apply exponent rule: [tex]\left(\frac{a}{b}\right)^c=\frac{a^c}{b^c}[/tex]
[tex]f(x)=4(\frac{1^2}{3^2})x[/tex]
[tex]f(x)=4(\frac{1}{9})x[/tex]
[tex]f(x)=\frac{4x}{9}[/tex]
Hence, the required function is [tex]f(x)=\frac{4x}{9}[/tex]
Answer:
f(x)=4([tex]\frac{1}{9}[/tex])^x
Step-by-step explanation: